'If I had my way, I'd have been a killer': songwriting and its motivations for leisure and work. Issue 2 (3rd April 2017) - Henderson, Stephen; Spracklen, Karl
ABSTRACT: This paper builds on our earlier work which looked at folk musicians exercising agency in careers that can develop from casual leisure through serious leisure to work. In looking specifically at songwriting, it synthesises theories on the underlying motivations reflecting the view of Born who suggests that the 'theory of cultural production requires reinvention' citing key themes of 'aesthetics and the cultural object; agency and subjectivity; the place of institutions; history, temporality and change; and problems of value and judgement'. It examines in a phenomenological way, through songwriter interviews, the cultural production of songs and the motivational factors within the songwriting process. Highlighting that this form of cultural production challenges, the hierarchical view of Maslow's needs and suggests that the career arc proposed by Stebbins is not a case of work simply following sequentially from serious and casual leisure.